Evaluasi Kebijakan Pengelolaan Limbah Batik di Kota Pekalongan - Syarifa Khasna (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
Development of batik industry in Pekalongan have diverse effects. From the economic improvement to environmental issues. Batik industry producing waste that could potentially pollute the environment. So, The Government of Pekalongan made local regulation about Protection and Environmental Management Pekalongan. The purpose of this policy is to create the environment Pekalongan good and healthy. Various efforts have been made by the government to decrease the pollution with installation of waste water management. This study discuss about policy evaluation batik-waste management in Pekalongan. In order to explain the results of the policy evaluation batik waste management used a qualitative research method. Subjects in this study is the government represented by the Environment Agency Pekalongan, batik entrepreneurs and communities. The method of data collection is through interviews and observations made by the selection of respondents using purposive sampling method. Based on the evaluation by Inputs, Process, Outputs, Outcomes can be concluded that the batik-waste management policy in Pekalongan unsuccessful. It is caused by several factors such as the limited funds so that complicates the motion of the government to make some facilities and also of the low participation of batik businessman in Pekalongan.